Pollination services of Tetragonula laeviceps Smith (Apidae: Meliponinae) on melon plants (Cucumis melo L.) - Bahlis, Wisda; Atmowidi, Tri; Priawandiputra, Windra (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Melon plants (Cucumis melo L.) have male, female, and hermaphrodite flowers. To optimize the pollination process, melon needs pollinating agents. Tetragonula laeviceps is a stingless bee species that play as an agent of pollination. This study aimed to measure the pollination services of T. laeviceps in melon plants in the greenhouse. Observation of visiting activity of bee using focal sampling method showed that the highest number of flowers visited by T. laevceps was 6.40 flowers/5 minutes. The longest visit duration of T. laeviceps was 28.04 seconds/flower. Visiting activity of T. laeviceps significantly correlated with environmental factors such as the air temperature and humidity (P<0.001). The pollen load on T. laeviceps was 26,200 pollen grains per individual. Pollination by T. laeviceps increased the fruit size, fruit weight, number of seeds per fruit, seed germination, and fruit sugar content compared with control treatment. Our result indicated that the pollination services of T. laeviceps can be applied in melon farms to improved production quality.